(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
In the last two decades genetic research achieved very significant results. In 2015, only few years since the completion of the Human Genome Project, scientists launched new experimental studies to genetically modify the DNA sequence of human embryos. These scientific advances have raised several ethical concerns, promoting issues that involve both natural and human science– including legal studies. Law and ethics frequently have to address the issues originated from these innovations and finding a common toolset often proves to be an arduous task. Genetics has a transnational dimension, experiences a continuous and rapid evolution and spreads new unfamiliar concepts, which ask to be integrated in social and legal culture. Analyzing the path that conducted the US Congress to approve the Genetic Information Nondiscrimination Act of 2008, this essay assesses the most common problems in genetic information management in the legal field. In recent studies, the first issue concerns the qualification of genetic data, considering their legal value to identify possible suitable models of protection. With regard to this, U.S. genetic legislation originally presented two different complementary options — antidiscrimination and privacy laws. With the clear intent to foster genetic research and scientific investments, the Federal legislator decided to endorse the protection against discriminations — the most evident effects of the distort use of genetic information — moving privacy to the background. Nevertheless, the limited scope of the Act — health insurance and employment — and the rapid diffusion of genetic tests for extremely varied purposes stressed the loopholes of GINA, suggesting the need to address some issues through the different legal lens of data protection. For such reasons, the Congress, in 2016, introduced a new bill to handle the problem, considering, in particular, privacy in genetic research. Covering the misuses of genetic information safeguarding a lawful employment of data seems a possible way to encourage an aware usage of genetic tests and scientific techniques, taking advantage of their silver linings without harming fundamental rights.